8 - Au sortir d’une longue « nuit » institutionnelle, nouvelles transactions entre les politiques forestières et les sociétés rurales en RD Congo post-conflit: by Francis Lelo Nzuzi - Oyono Phil René (Africa Development, 2006)
Since 2002, the Democratic Republic of Congo (DR Congo), between ‘war and peace’, has a new Forestry Law. Among other innovations, this Forestry Law lays down the basis of a decentralization process for forestry management. In the logic of decision-makers, it is a tool for forest sustainability, economic recovery and the reconstitution of the territorial unity of the country, after waves of armed conflicts. This contribution presents the global context of recovery in DR Congo and characterizes the institutional and legal framework governing forest management in the country. A particular attention is paid to powers and responsibilities awarded to local communities. The article also analyses key opportunities and uncertainties related to such a decentralization trajectory.